2008
DOI: 10.1227/01.neu.0000316265.59596.8c
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Reliability of Endoscopic Third Ventriculostomy

Abstract: Age was the only factor statistically associated with the long-term reliability of ETV. Patients less than 6 months old had poor reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 44 publications
2
37
0
Order By: Relevance
“…38 More recent evidence from larger, and in one case, multicenter series has supported the finding that age is the main determinant of outcome with younger children, particularly neonates, faring worse. 39,40 The other standard technique of CSF diversion, a CSF shunt, has rarely been compared with ETV, with results suggesting no difference 41 or a slight advantage in terms of costeffectiveness for ETV. 42 CSF shunt outcomes are also known to be influenced by age, with younger children also faring more poorly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 More recent evidence from larger, and in one case, multicenter series has supported the finding that age is the main determinant of outcome with younger children, particularly neonates, faring worse. 39,40 The other standard technique of CSF diversion, a CSF shunt, has rarely been compared with ETV, with results suggesting no difference 41 or a slight advantage in terms of costeffectiveness for ETV. 42 CSF shunt outcomes are also known to be influenced by age, with younger children also faring more poorly.…”
Section: Discussionmentioning
confidence: 99%
“…Kadrian et al reported a strong effect of the patient's age on outcome. 40 The authors reported the percentages of patients "presumed to have a functioning ETV after 5 years" as follows: 41% in patients 1-to 6-month old at the time of surgery, 58% in patients 6-to 24-month old, and more than 70% in patients older than 24 months. These results correspond to the data reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…64 Jenkinson reported a 5.8% complication rate in 190 adult ETV procedures 65 and Kadiran described a 4.9% infection rate, 7.2% transient major complication rate, and a 1.1% permanent complication rate in 203 ETV patients. 23 In general, it has been reported that complication and mortality rates decrease with increased surgeon experience and are lower compared with open procedures in experienced hands. 47,66,67 A qualitative analysis of our study did show that complication rates marginally decreased as surgeon experience increased, but it is important to note that equipment quality also improved over the course of the series.…”
Section: Hydrocephalusmentioning
confidence: 99%
“…These include ETV and septostomy, options that are most suitable for treating those patients with obstructive hydrocephalus. [20][21][22][23][24][25][26][27][28][29][30] ETV consists of creating a hole through the tuber cinereum in the floor of the third ventricle to allow CSF to flow into the interpeduncular and prepontine cisterns, thereby bypassing obstructions in the aqueductal area, 21,31-40 whereas septostomy involves placing the hole in the septum pellucidum. Another postulated mechanism involves the restoration of the pulsatility of ventricular walls as a result of the stoma, an effect that may help restore CSF dynamics by driving CSF flow from the ventricular system into the subarachnoid space.…”
Section: Hydrocephalusmentioning
confidence: 99%
See 1 more Smart Citation